Predictors of inadequate bowel preparation for inpatient colonoscopy - Jawa, Hani; Mosli, Mahmoud; Alsamadani, Wafaa; Saeed, Sundus; Alodaini, Rahaf; Aljahdli, Emad; Bazarah, Salim; Qari, Yousef (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Adequate colonic cleansing is essential for achieving effective and safe colonoscopy. Inpatient status is one of several factors associated with poor bowel preparation leading to incomplete colonoscopy procedures, which in turn may cause increased patient morbidity, missed pathology, prolonged hospital stay, and increased cost. The aim of this study was to identify predictors of inadequate bowel preparation for inpatient colonoscopy. Materials and Methods: Medical records of inpatients who underwent colonoscopy at a university hospital between January 2015 and June 2016 were reviewed. Logistic regression analysis was used to identify predictors of “inadequate” bowel preparation. Odds ratios (OR) with 95% confidence intervals (CI) were reported. Results: We included 130 patients in the analysis with a mean age of 58.2 (17.3) years. Fifty-seven percent of the patients underwent the procedure before noon, and the remaining between noon and 4 pm. The most common indications for inpatient colonoscopies were gastrointestinal bleeding and screening for colorectal cancer, and the majority of patients received meperidine for sedation (38.5%). The overall bowel preparation success rate was 57%, and the success rate was higher in the morning procedures compared to the afternoon procedures (71% vs. 46%, p=0.004). Regression analysis identified procedure time as a significant predictor of bowel preparation success such that procedures performed in the afternoon had lower chances of success (OR=0.32, 95% CI=0.14-0.74, p=0.007). Aspirin use was also a positive predictor for bowel preparation success (OR=3.1, 95% CI=1.03-9.24, p=0.044). Conclusion: Incomplete colonoscopies for inpatients due to inadequate bowel preparation are very common. Procedures performed in the afternoon are less likely to be successful. Cite this article as: Jawa H, Mosli M, Alsamadani W, et al. Predictors of inadequate bowel preparation for inpatient colonoscopy. Turk J Gastroenterol 2017; 28: 460-4.